УДОСКОНАЛЕНА МАТЕМАТИЧНА МОДЕЛЬ ЗАСОБУ ВИМІРЮВАННЯ ПУСКОВОГО МОМЕНТУ ЕЛЕКТРОДВИГУНІВ - Васілевський, О.М. (Інститут електродинаміки НАН України, Київ, 2013)
Was further developed metematichny apparatus that describes measuring operations taking place in the facility measuring starting torque motors. Advanced mathematical model to improve the accuracy of the starting torque and explore the dynamic and static metrological characteristics of measuring the starting torque motors. Found that the relative error methodical improved mathematical model measuring means does not exceed 8%, after the transition, as compared with an idealized (teoertichnim) value of the input (measured) signal indicating sufficient matching theoretical statements proposed mathematical model developed starting torque measuring means. References 10, figures 5.